English Morphological Awareness of EFL University Students during Blended Learning Implementation - Suadi Suadi (Pioneer: Journal of Language and Literature, 2022)
This study is aimed to investigate the English morphological awareness of EFL university students during blended learning due to the covid-19 pandemic. A mixed-method was employed and 17 students were willing to be participants. This study applied an online test to obtain quantitative data and an online open-ended questionnaire to gain qualitative data. The results demonstrated that (1) 10 students (58.8%) were categorized as moderate in English morphological awareness skills, 5 students (29.4%) were perceived high criteria and only 2 students (11.8%) were ranked low category. (2) 17 students expressed their opinion on the English learning experience during blended learning implementation due to the covid-19 pandemic which has a connection to morphological awareness. Their views are generally summarized as follows; they admitted that they actively self-studied at home, preferred offline learning to online learning, frequently practiced English at home, seldom read English books and most of them made extensive use of social media and the internet to access English learning content. The results of this study can be concluded that the English learning environment and recent technologies such as social media and the internet, could have a significant impact on building and improving students’ English morphological awareness.